Child psychopathology - Mash, Eric J.; Barkley, Russell A. (Guilford Press, 2014)
"Now in a fully revised and updated second edition, this authoritative text integrates state-of-the-art theory and empirical research on a wide range of child and adolescent disorders. Featuring contributions from leading scholars and clinicians, the volume is notable for its comprehensive coverage of the biological, psychological, and social-contextual determinants of childhood problems. Each chapter focuses on a specific disorder, describing its characteristics, developmental course, and epidemiology; outlining current diagnostic and classification schemes; identifying risk and protective factors; and discussing implications for prevention and treatment. Including a new chapter on adolescent substance use disorders, the second edition has been updated throughout to reflect important advances in the field. Incorporated is emerging knowledge in the areas of neurobiology, genetics, developmental psychology, and emotions, as well as new findings on sex differences in psychopathology and long-term outcomes for children at risk"--